Pelatihan Peningkatan Kapasitas Pekerja Wanita Dalam Mengidentifikasi Keluhan Kesehatan Akibat Paparan Pestisida di Perkebunan Sawit Sumatera Selatan - Maksuk, Maksuk; Haryati; Salma Rizkiya Kinasih (Poltekes Kemenkes Tanjungpinang, 2025)
Female workers on palm oil plantations are at high risk of pesticide exposure due to their involvement in spraying, fertilizing, and plant care activities. Pesticide exposure can cause various health problems, including disorders of the nervous system, respiratory, reproductive, cancer and other chronic diseases. This activity aimed to improve the capacity of female workers to recognize the dangers of pesticides, identify early symptoms of poisoning, and implement appropriate self-protection measures. The training was conducted through interactive methods, including education, discussion, and presentation of group discussion results regarding health complaints experienced while working on oil palm plantations. The results of the activity showed an increase in participants' knowledge and skills in recognizing health risks due to pesticides and knowing the procedures for reporting health complaints in the workplace. With this training, it is hoped that female workers on oil palm plantations can be more aware of the importance of self-protection, be able to identify early symptoms of pesticide poisoning, and contribute to creating a healthier and safer work environment.